Aplicação a produtos longos de modelo matemático elaborado para laminação a quente de produtos planos - Tassia Ribeiro Salles Moura (2017)
The use of microalloying elements along with a thermomechanically controlled hot rolling with the aid of a mathematical modeling tool has been traditionally used in the production of flat products with improved mechanical properties. However, this concept has not yet been applied in the production of long products. The goal of this study was to apply in an industrial line of hot rolling long products a mathematical model developed for flat products. Data from an experimental industrial trial, wire rod rolling machine microalloyed Nb steel, were used in this work for mathematical modeling of evolution of austenite grain size in this process. It was used a mathematical model, the Microsim®, to calculate the evolution of grain sizes along the rolling process. This model was originally developed for hot rolling of flat products being this the first report in which this is this model has been applied to a long product hot rolling process. The Microsim® is also a mathematical model that considers a distribution of austenitic grains at each pass rather than an average grain size to simulate the rolling process. The embodiment of the industrial experiment allowed sampling of points where the process billet being rolled to wire rods had dimensions of 40, 16 and 5 mm. These samples were quenched and the austenitic grain sizes were measured. This then has an opportunity to check whether the model being used was in fact consistent forecasts. In general, the predictions carried out by making use of the model were consistent with the values shown by austenitic grain sizes measurements in the industrial experiment. Moreover, the results obtained from the simulation also demonstrate the importance of using a mathematical model to consider a distribution of grains. It can be seen that 40 mm bars had a greater dispersion of grain sizes around the median grain size than in the case of bars of 16 mm diameter. On the other hand, when the gauge has reached the wire rod diameter, the total strain applied was far greater than the one at rolling of flat products, that the effect was to homogenize the distribution of grain sizes about the mean, producing a very fine grain in approximately 5 and a small dispersion.